Determinan Generasi Y Terhadap Minat Pembelian Rumah Pada KPR Syariah - Ani Nurhayati Taufik; Yono Haryono (Indonesian Journal of Islamic Economics and Business, 2021)
The research aims to find out how personal variables consisting of religiosity and income factors, social variables consisting of friend, parent, and individualism factors, and internal variables of Islamic banks consisting of price, bank image, service, and promotion factors influence home purchase decisions through KPR Sharia in Generation Y domiciled in Jabodetabek. This research uses explanatory method to obtain information about the description of the factors that influence home purchase decisions through Sharia Mortgages. This research was conducted by distributing questionnaires to 100 selected respondents who fit the research criteria. The analysis method used is Structural Equation Modeling (SEM) using Partial Least Square (PLS). The results of the study show that the influence of personal and social variables on house purchase decisions through KPR Sharia is positive but not significant it shows that the factors related to religiosity, income, parent factors, friends, and individualism do not significantly influence the decision generation Y to apply for a KPR through a Sharia Bank. The internal variables of Islamic banks have a positive and significant influence on house purchase decisions through Sharia Mortgages, it shows that the factors related to prices, bank images, services and promotion of Sharia Bank Mortgages products determine the prospective customers, especially in terms of this is Generation Y to apply for a KPR through a Sharia Bank.